Addressing domestic violence against women: a case study of Navio traditional council in Kasena-Nankan West District of the Upper East Region, Ghana. - Thomas, Amibase (2020)
A thesis submitted to the School of Public Health, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MPH Health Education and Promotion.